Market Orientation’s Effect on Customer Value, Trust, Satisfaction, and EWOM when using the MRT (International Journal of Scientific Research and Management (IJSRM), 2024)
The purpose of this study is to ascertain how market orientation affects customer value, trust, contentment, and word-of-mouth when using mass transit. MRT users comprised the study’s demographic. Passengers who had taken the MRT more than twice were given a sample of 224 individuals by purposeful sampling. With the usage of smartPLS software, structural equation modeling, or SEM, is the analytical technique employed. According to the study’s findings, market orientation significantly affects customer value, trust, contentment, and word-of-mouth when utilizing the MRT, both directly and indirectly. Effective marketing tactics and market orientation can enhance customer value perception, trust, and user pleasure. Relevant stakeholders and business practitioners can better grasp how maximizing market orientation fosters positive interactions with MRT users thanks to the research’s findings. These findings’ practical applications can aid in the creation of more potent marketing campaigns and enhance the general MRT user experience.